Approximate controllability of second order dynamical systems - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
In the paper linear, infinite-dimensional second-order dynamical systems defined in a separable Hilbert spaces are considered. U sing the spectral theory for linear, unbounded operators, necessary and sufficient conditions for various types of approximate controllability are formulated and proved. As an illustrative example approximate controllability of flexible mechanical dynamical system described by linear partial differential equations is investigated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka